2013
DOI: 10.2478/s11535-013-0180-7
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the structure and secretory activity of the androgenic gland of Travancoriana schirnerae

Abstract: This study investigated the seasonal variation in the structure and secretory activity of the androgenic gland (AG) in the freshwater crab: Travancoriana schirnerae. The androgenic gland is an elongate structure, attached to one side on the wall of the ejaculatory duct. Histological studies showed the presence of three cell types, which differ in size, shape of nuclei, and presence or absence of secretory vesicles. Type I cells are small with large nuclei whereas type II cells are large with small nuclei. Type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
(50 reference statements)
0
4
0
1
Order By: Relevance
“…In the current investigation, bilateral eyestalk ablation induced hypertrophy and hyperplasia of the AG during the active phase as evidenced by increase in width of the gland, thickness of the connective tissue layer, increase in cell and nuclear diameter with predominance of type I cells. Comparable results were obtained by Demeusy (1960) in C. maenas where removal of eyestalks led to hypertrophy of the AG, signified by ultrastructural features related to hyperactivity. Removal of eyestalks caused hypertrophy and hyperplasia of the gland in the crabs Scylla serrata, R. harrisii, C. sapidus and the shrimp Lysmata seticaudata (Rangnekar et al, 1971;Payen et al, 1971;Touir, 1973).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In the current investigation, bilateral eyestalk ablation induced hypertrophy and hyperplasia of the AG during the active phase as evidenced by increase in width of the gland, thickness of the connective tissue layer, increase in cell and nuclear diameter with predominance of type I cells. Comparable results were obtained by Demeusy (1960) in C. maenas where removal of eyestalks led to hypertrophy of the AG, signified by ultrastructural features related to hyperactivity. Removal of eyestalks caused hypertrophy and hyperplasia of the gland in the crabs Scylla serrata, R. harrisii, C. sapidus and the shrimp Lysmata seticaudata (Rangnekar et al, 1971;Payen et al, 1971;Touir, 1973).…”
Section: Discussionmentioning
confidence: 56%
“…Several authors suggested that the AG is under the control of an inhibitory neuropeptide -GIH, secreted from the XO-SG complex of the eyestalks. Demeusy (1953) and Demeusy and Veillet (1958) have observed that secretory activity of the AG is directly regulated by the influence of GIH in C. maenas. Similar observations were recorded by Hoffman (1968) in P. platyceros.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Santos et al., ; Goldstein & Dupré, ; Shinozaki‐Mendes et al., ;. Zara et al., ; Devi & Smija, ; Wang et al., ).…”
Section: Discussionunclassified
“…Santos et al, 2009;Goldstein & Dupré, 2010;Shinozaki-Mendes et al, 2012;. Zara et al, 2012;Devi & Smija, 2014;Wang et al, 2015). The morphology of the testes, according to Nagao and Munehara (2003), can be classified as tubular or lobular.…”
Section: Discussion 41 | General Morphologymentioning
confidence: 99%